Post-abortion contraceptive use among women purchasing medication abortion from pharmacies vs. clinics: Evidence from Cambodia and Ghana - Pearson, Erin; Menzel, Jamie; Mao, Bunsoth; Agula, Caesar; Antobam, Samuel; Eckersberger, Elisabeth; Bawah, Ayaga; Saphonn, Vonthanak; Kapp, Nathalie (Contraception (Stoneham), 2026)
To understand differences in post-abortion contraceptive use between women accessing medication abortion (MA) in pharmacies compared to clinics. We conducted secondary analysis of data from two non-randomized non-inferiority trials that compared MA outcomes for pharmacy and clinic clients in Cambodia (2018–2019) and Ghana (2019–2021). A total of 3791 MA clients (clinic: n = 1966, pharmacy: n = 1825) were recruited from 60 urban sites (24 clinics, 36 pharmacies). We used Poisson models to assess differences in post-abortion contraceptive use between pharmacy and clinic clients and mediation analyses to explore the mechanisms through which MA purchase location influences post-abortion contraceptive outcomes. Contraceptive use 30 days post-abortion was reported by approximately half of clinic clients (Cambodia: 51.9%; Ghana 41.3%) and somewhat fewer pharmacy clients (Cambodia: 43.0%; Ghana: 27.0%), but this difference was not statistically significant (Cambodia: adjusted risk difference [aRD] = −6.6%; 95% CI: −16.4% to 3.3%; Ghana: aRD = −10.1%; 95% CI: −23.4% to 3.2%). Though overall post-abortion contraceptive use was comparable, pharmacy clients used less effective contraceptive methods than clinic clients. Offer of contraceptive information and methods at the point of MA purchase were significantly higher in clinics, and mediation analyses demonstrated that this explained differences in post-abortion contraceptive outcomes between pharmacy and clinic clients. Use of more effective post-abortion contraceptive methods may be facilitated by offering contraceptive information and methods in pharmacies at the point of MA purchase, but further research and monitoring is required to ensure that these interventions are client-centered and not coercive. Greater access to contraceptive information and methods in pharmacies at the point of MA purchase may facilitate use of effective post-abortion contraceptive methods for those self-managing their abortions via pharmacy purchase of MA.